2018
DOI: 10.1002/14651858.cd011292.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity for women with breast cancer after adjuvant therapy

Abstract: No conclusions regarding breast cancer-related and all-cause mortality or breast cancer recurrence were possible. However, physical activity interventions may have small-to-moderate beneficial effects on HRQoL, and on emotional or perceived physical and social function, anxiety, cardiorespiratory fitness, and self-reported and objectively measured physical activity. The positive results reported in the current review must be interpreted cautiously owing to very low-to-moderate quality of evidence, heterogeneit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
151
3
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(182 citation statements)
references
References 287 publications
7
151
3
7
Order By: Relevance
“…The National Institute for Health and Care Excellence and the World Health Organisation recommend that all adults should participate in at least 150 minutes of moderate intensity physical activity per week. The benefits of physical activity in individuals receiving adjuvant cancer treatment are reported within the literature, including improvements in quality of life, physical functioning, and cardiorespiratory fitness, as well as reduced fatigue . Consequently, physical activity is an internationally recognised recommendation for individuals with cancer, including women undergoing adjuvant treatment for breast cancer…”
Section: Introductionmentioning
confidence: 99%
“…The National Institute for Health and Care Excellence and the World Health Organisation recommend that all adults should participate in at least 150 minutes of moderate intensity physical activity per week. The benefits of physical activity in individuals receiving adjuvant cancer treatment are reported within the literature, including improvements in quality of life, physical functioning, and cardiorespiratory fitness, as well as reduced fatigue . Consequently, physical activity is an internationally recognised recommendation for individuals with cancer, including women undergoing adjuvant treatment for breast cancer…”
Section: Introductionmentioning
confidence: 99%
“…The difference in our findings from previous research may be due to our use of a measurement tool specific to physical activity. Previous research demonstrating significant differences in quality of life between breast cancer survivors and healthy women has used general quality of life tools such as the SF‐36 (Duijts et al, ; Fong et al, ; Hoyer et al, ; Koch et al, ; Lahart et al, ). General quality of life tools include items related to physical activity, but also include disease or general health‐related items that may selectively affect clinical populations experiencing physical and social difficulties due to disease states.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity improves quality of life in healthy women (Chin, van Poppel, Twisk, & van Mechelen, ; Rezende Barbosa et al, ) and can also improve quality of life in breast cancer survivors (Duijts, Faber, Oldenburg, van Beurden, & Aaronson, ; Fong et al, ; Lahart, Metsios, Nevill, & Carmichael, ; Mishra et al, ). However, in breast cancer survivors, quality of life is most often measured with general or disease‐specific quality of life tools that are not directly related to physical activity (Chopra & Kamal, ; Maratia, Cedillo, & Rejas, ; Pusic et al, ), and so may not accurately reflect physical activity‐related quality of life (PAQOL).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise training and dietary interventions have been suggested to alleviate or minimize treatment‐related side effects to BC. Recent systematic reviews and meta‐analysis have shown significant effects of physical exercise on anthropometric measures and quality of life . The ENERGY study is the largest weight loss intervention trial among survivors of BC to date, including both dietary guidance and physical activity to promote weight loss over a 2 year period, resulting in a ~4% weight loss among elderly overweight or obese women .…”
Section: Discussionmentioning
confidence: 99%